Sustaining and Impeding Factors of Microfinance Services for Micro-enterprises Development - Sharma, Ph. Romen; Singh, Rashmi; Dubey, Shantanu Kumar; Patil, Shridhar (Indian Journal of Extension Education, 2013)
The present study examines the sustaining and impeding factors of the microfinance services as perceived by the  beneficiaries and dropout clients, and it also investigates the reason for not availing the microfinance services by the non beneficiaries. Study included 40 microfinance beneficiaries, 30 microfinance drop-outs and 30 non-beneficiaries  constituting the total sample of 100 respondents. Responses of the subjects were collected through an open ended  questionnaire. Garrett's ranking was used to rank order the factors. The study revealed that ease of access and related  services of micro-credit at village level and lower capital interest rate were the sustaining factors whereas insensitivity of  microfinance institution (MFI) to type of enterprises, business cycle, clients' socio-economic and -personal  circumstances; the norm of weekly repayments and savings pressure were the impeding factors. Fear of losing their  property at default repayment and perceived weekly repayments pressure were the reasons for not availing the  microfinance services.
Keywords: Microfinance; micro-enterprises; sustaining factors; impeding factors